One-Haptic Fixation of Posterior Chamber Intraocular Lenses without Scleral Flaps - Ashraf I. Moawad; Asaad A. Ghanem (Journal of Ophthalmology, 2012)
Purpose. To assess visual results and complications of a modified technique of posterior chamber intraocular lenses (PC IOLs) in aphakic eyes without scleral flaps. Methods. Modified one-haptic scleral fixation was performed in one eye each of 25 patients with aphakia and insufficient capsule support. Follow-up period was six months. Outcome measures included best-corrected visual acuity, intraocular pressure (IOP), and postoperative complications. Results. The study included 15 males and 10 females. The preoperative best-corrected visual acuity (BCVA) ranged from 5/60 to 6/9. The operation time ranged from 25 to 45 minutes (mean 35.25 ± 5.34 min). Anterior vitrectomy was performed in 12 cases (48%). There was no major IOL decentration. The final BCVA ranged from 6/36 to 6/9. Seven cases (28%) showed postoperative glaucoma, five cases (20%) had temporary hypotony, and hyphema in 2 eyes (8%). No cases of suture erosion, postoperative endophthalmitis, retinal detachment, or IOL dislocation were detected. Conclusion. This technique of one-haptic scleral fixation of posterior chamber IOLs is a good choice in presence of insufficient capsule support. It reduces the operation time, achieves the IOL stability, and minimizes postoperative suture-related complications.